A CLINICAL EVALUATION OF ANTIMICROBIAL ACTIVITY OF GOMUTRA ARKA IN DUSTA VRANA (International Journal of Ayurveda and Pharma Research, 2020)
Vrana chikitsha is very significant in field of Shalya tantra. Healing of Vrana is depends on many factors. Among them growth of microorganism play essential role to slow the process of healing. In Dusta Vrana to improve the healthy granulation and to reduce the colony count of microorganism specific Krimghna dravya is required for that in Shasthi upkrama under Krimighna karma Gomutra Arka is advised. Which has additional property of Lekhana and Ropana. Gomutra Arka is given importance in many oral classical formulation of Ayurveda to treat the Krimi, which is not evaluated for local application on Dusta Vrana yet.Materials and Methods: A simple randomized controlled clinical study where 50 patients were equally divided as group A: Gomutra Arka (trial drug) and Group B: Povidone-iodine (standard drug) for 14 days. Observations and results: The study result revealed that Gomutra Arka proved to be better Antimicrobial agents than povidone-iodine with a highly significant p-value of 0.04 in comparison to 0.68. It was also established in the study that 10mlGomutra Arka proved to be more effective on different microorganisms that are Staphylococcus Aureus, Pseudomonas Aeruginosa, Shigella, Salmonella, E. Coli, and Candida Albicans. Conclusion: The Gomutra Arka acts as an antimicrobial agent due to its property like Katu tikta kashya rasa which are Krimighna in nature by this inhibition of microorganism could happen also due to the Ushna tikshna and Kshara guna gives unfavorable environment for bacterial growth. The presence of constituents like copper, aurum, urea, ammonia further helps in antimicrobial activity. Therefore, Gomutra Arka can be used in regular practice as its available at a low cost, affordable and the study proves its efficiency over the Povidone-iodine controlled group.